Panama's Growth Prospects : Determinants and Sectoral Perspectives - Beaton, Kimberly; Hadzi-Vaskov, Metodij (Washington, D.C. : International Monetary Fund, 2017)
This paper estimates medium-term potential growth for a country undergoing significant structural and secular changes. Our forward-looking framework, incorporating three analytical approaches for examining economic prospects, constitutes an important complement to typical backward-looking methods that filter or extrapolate historical data. In particular, the opening of the expanded Panama Canal in 2016 highlights significant structural changes underway in the Panamanian economy. We first analyze growth determinants and find that Panama is well-placed to maintain its business model, with improvements in education and governance important to support growth. Second, the current pipeline of investment projects can help sustain investment-led growth, although at a more moderate pace. Third, further development of the logistics and tourism sectors holds promise to further build on Panama's comparative advantage.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet